ORGANIZATIONAL CLIMATE, TEACHER EMPOWERMENT, WORK MOTIVATION AND ICT EFFECTIVENESS IN IMPROVING TEACHER PERFORMANCE - Rika Widiastuti; Soewarto Hardhienata; Rais Hidayat (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
Teacher performance plays a critical role in improving educational quality, particularly in vocational schools facing rapid curricular and technological changes. This study examines the direct and indirect effects of organizational climate, teacher empowerment, work motivation, and ICT effectiveness on teacher performance in private vocational schools. A quantitative survey design was employed involving 156 permanent teachers from private vocational schools in Pontianak City, Indonesia. Data were collected using validated questionnaires and analyzed through path analysis and Sobel tests to identify mediating effects. The findings indicate that organizational climate, teacher empowerment, work motivation, and ICT effectiveness have significant direct effects on teacher performance. Furthermore, work motivation and ICT effectiveness mediate the relationships between organizational climate and teacher empowerment on teacher performance. The Scientific Identification Theory to Conduct Operation Research in Education Management (SITOREM) method was applied to determine priority indicators for improvement. This study contributes to educational management literature by proposing an integrated model of teacher performance and providing strategic recommendations for vocational education institutions